2018
DOI: 10.1590/2237-6089-2017-0153
|View full text |Cite
|
Sign up to set email alerts
|

Does CBT have lasting effects in the treatment of PTSD after one year of follow-up? A systematic review of randomized controlled trials

Abstract: Introduction: While several previous meta-analyses have documented the short-term efficacy of cognitive-behavioral therapy (CBT), its long-term efficacy remains unknown. Posttraumatic stress disorder (PTSD) is a serious, debilitating, often chronic and disabling disease. Objective: To estimate the long-term efficacy of CBT in the treatment of PTSD by assessing the maintenance of the effect after one year of follow-up. Method: We performed a systematic review through electronic database searches including ISI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…A number of meta-analyses and systematic reviews have supported the effectiveness of psychological treatments, especially CBT, for people with PTSD ( 26 ). Our previous randomized controlled studies also suggested that CBT was effective at reducing PTSD symptoms ( 27 , 28 ). In this follow-up study, we found that CBT emerged as a significant predictor of a reduction in PTSD symptoms, explaining a significant 33.6% of the variance.…”
Section: Discussionmentioning
confidence: 87%
“…A number of meta-analyses and systematic reviews have supported the effectiveness of psychological treatments, especially CBT, for people with PTSD ( 26 ). Our previous randomized controlled studies also suggested that CBT was effective at reducing PTSD symptoms ( 27 , 28 ). In this follow-up study, we found that CBT emerged as a significant predictor of a reduction in PTSD symptoms, explaining a significant 33.6% of the variance.…”
Section: Discussionmentioning
confidence: 87%
“…Other possible explanations or contributory factors are the slightly lower levels of education and greater physical comorbidity in the GSH group; both have previously been found to influence treatment outcome. 16,53 Further improvement after face-to-face CBT-TF has been found before 85 and has been hypothesised to be due to ongoing trauma processing and practise of techniques learnt in treatment.…”
Section: Results In the Context Of Other Researchmentioning
confidence: 97%
“…Studies have shown that CBT is effective in the post-treatment phase of PTSD, indicating that its effects endure [68]. In addition, cognitive control network activity is increased in patients with major depression and PTSD, suggesting that CBT may have a beneficial effect on the severity of symptoms [69].…”
Section: Research Question 6 [Rq6]mentioning
confidence: 99%